(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
This article uses a fictitious interpretation of the image of Alexander in the story of the Uzbek writer Rakhimjon Ataev “Haddy Iskandari”. This article also shows the courage of the brave, brave, and courageous people of the country.